A Contemporer Design of Karunia Memorial Park and Green Crematorium in Medan: Contemporer Design of Karunia Memorial Park and Green Crematorium in Medan - Chintya, Chintya; Sitorus , Rudolf (Jurnal Koridor, 2022)
Death is not the end. Quoting from Chuck Palahniuk, â€œWe all die. The goal isnâ€™t to live forever, the goal is to create something that will.â€ It means, death is something certain dan the goal in life isnâ€™t to live in eternity but to create something that will be eternal. In Karunia Memorial Park and Crematorium together we create eternity. Funeral ceremonial is very important for chinese born Indonesian (Tionghoa) as it is believed to be showing their respect to their anchestors. To create a design that could fulfilled oneâ€™s needs and solved oneâ€™s problem author had analyzed the pros and cons of traditional Tionghoaâ€™s cemetery. The site is located in Medan Tuntungan, Simalingkar B. Focusing on Feng Shui, the shape of the building itself was taken from yin-yang and the number eight that are considered as a lucky number. Not only the green burial and green cremation as the main focus. Implemented the advanced of Virtual Reality Techonology is one of the catch. Through this design, it is hoped to increase not only the society awareness of the importance of the environment and chinese culture but also sublimated everyone.